Analisis Hak Asasi Manusia dalam Kejahatan Tindak Pidana Korupsi Bantuan Sosial Penanganan Covid-19 (Studi Kasus Korupsi Bantuan Sosial Penanganan Covid-19 Oleh Kementerian Sosial) - Andhonios Joudy, Elnando; Susetyo, Heru (LPPM Universitas Ekasakti Padang, 2024)
Corruption has become a deep-rooted problem in Indonesia. Even when the Covid-19 pandemic affected Indonesia, the implementation of Social Assistance (Bantuan Sosial) became a field for the practice of corruption. The corruption committed by irresponsible parties, certainly led to the intersection of human rights, especially during the Covid-19 pandemic. The problems in this study are (1) how is the regulation of human rights aspects in the national and international Corruption Eradication instruments; and (2) how is the analysis of human rights enforcement for the community and the perpetrators in the case of corruption in social assistance during the disaster period. In order to answer these problems, this research will be analyzed using doctrinal research methods.